Preliminary longitudinal report on symptom outcomes in symptomatic and asymptomatic women with imaging evidence of temporomandibular joint arthritic changes - Schmitter, Marc; Wacker, Katrin; Pritsch, Maria; Giannakopoulos, Nikolaos Nikitas; Klose, Christina; Faggion Junior, Clóvis Mariano; Kress, Bodo; Leckel, Michael; Rammelsberg, Peter (The international journal of prosthodontics, 2010)
The objectives of this preliminary, longitudinal, and explorative cohort study were to assess changes in and the onset of osteoarthrosis (OA)-related pain in the temporomandibular joint (TMJ) and to address factors that might impact the development or reduction of associated pain symptoms.
Gesehen am 15.06.2023